Conversations in transition : leading South African voices - Villa-Vicencio, Charles; Soko, Mills (Cape Town, South Africa : David Philip, 2012)
"The conversations in this book are with a cross-section of South Africans from very different backgrounds, whose journeys in life have taken them in different directions. They are influential people located in different layers of South African life, most of whom hearteningly acknowledge the need to understand the mental and emotional spaces of other South Africans. The common ground between them, expressed through a mixture of styles, dreams and desires, as well as fears and uncertainties, is an expectation that the country has the potential to do better. These are strong voices. At times they are strident and at times they border on the utopian. In most cases their views are infused with political realism. This, encouragingly, suggests that there are significant South Africans in most spheres of society who are more ready to undertake a national self-reckoning exercise than the heat of public debate sometimes suggests. This work is therefore not just a collection of interviews with eminent leaders, but a forceful profile of our democracy in its second decade. It is, among other things, also a truthful look at our faults and follies, accomplishments and achievements." -- Publisher's note.
Keywords: Interviews -- South Africa; Politicians -- South Africa -- Interviews; Civic leaders -- South Africa -- Interviews; Labor union members -- South Africa -- Interviews; Businesspeople -- South Africa -- Interviews; Judges -- South Africa -- Interviews; Religious leaders -- South Africa -- Interviews; Democracy -- South Africa